Use Of Code Switching And Code Mixing In Daddy Corbuzier's Podcast : Jujurly Livy Renata - Lilis Dwi Anzani; Safnah Sagala; Vera Adzani; Achmad Yuhdi (International Journal of Multilingual Education and Applied Linguistics, 2024)
This research aims to describe the forms of code switching and code mixing, and describe the factors that cause code switching and code mixing in Daddy Corbuzier's podcast: Honestly Livy Renata. The research method used in this research method is a qualitative descriptive method. From this analysis, it was found that there were 9 code-switching utterances and code-mixing utterances in the video.